CONTEMPORARY METHODS OF LEARNING ENGLISH MORE EFFECTIVELY - Olimjonova Farangiz; Durdona Khamidova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
The article is devoted to the consideration of various, in our opinion, effective ways of learning English. The publication examines the possibilities of using proprietary techniques that contribute to the rapid learning of foreign languages, and in particular English.